Characterization of Fermented Product from Shrimp Waste and Anchovy (Stolephorus sp.) - Siti Tsaniyatul Miratis Sulthoniyah; Nandya Fitri Rachmawati; Cici Agustin; Susi Santi; Yoga Aditya (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
The abundance of shrimp waste is a problem that has not yet been completely resolved and research is still ongoing. One effort that can overcome this problem is to use it as a raw material for making shrimp paste. The purpose of this research was to utilize shrimp shell waste as a food additive. The research method used was experimental with five treatments, namely A1B1 (0:100), A2B2 (25:75), A3B3 (50:50), A4B4 (75:25) and A5B5 (100:0). Meanwhile, storage time was P1 (1 day), P2 (4 day), P3 (7 day) and P4 (30 day). The tested parameters were moisture content, pH and organoleptic (descriptive). The results showed that the best formulation was the ratio of shrimp shell waste and anchovy of 25:75 (A2B2) with P3 storage time. The value of moisture content was 8.1% and pH was 7,3. The smell of shrimp paste was not too strong with a reddish yellow color and a slightly rough texture.